2015
DOI: 10.1155/2016/2827567
|View full text |Cite
|
Sign up to set email alerts
|

Administration of a Polyphenol‐Enriched Feed to Farmed Sea Bass (Dicentrarchus labrax L.) Modulates Intestinal and Spleen Immune Responses

Abstract: Farmed fish are exposed to a continuous antigenic pressure by microbial and environmental agents, which may lead to a condition of chronic inflammation. In view of the notion that polyphenols, largely contained in fruits and vegetables, are endowed with antioxidant and anti-inflammatory activities, farmed sea bass (Dicentrarchus labrax L.) have been administered with red grape polyphenol-enriched feed. Polyphenols were extracted from the seeds of Canosina Nero di Troia Vitis vinifera and mixed with conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…Various measures have been introduced over the years to proffer solutions to these negative effects such as the use of antibiotics, anthelmintic agents and hormones (Cabello, 2006; Fawole, Sahu, Pal, & Ravindran, 2016). However, the frequent use of antibiotic has led to the development of drug‐resistant pathogens, complications in human health, bioaccumulation and ecosystem pollution (Arciuli et al, 2017; Cabello, 2006; Magrone et al, 2016). Nevertheless, the needs for the production of antibiotic‐free animal protein and increased awareness of organic food have led to an upsurge in the use of medicinal plants or phytogenic as feed additive in aquaculture.…”
Section: Introductionmentioning
confidence: 99%
“…Various measures have been introduced over the years to proffer solutions to these negative effects such as the use of antibiotics, anthelmintic agents and hormones (Cabello, 2006; Fawole, Sahu, Pal, & Ravindran, 2016). However, the frequent use of antibiotic has led to the development of drug‐resistant pathogens, complications in human health, bioaccumulation and ecosystem pollution (Arciuli et al, 2017; Cabello, 2006; Magrone et al, 2016). Nevertheless, the needs for the production of antibiotic‐free animal protein and increased awareness of organic food have led to an upsurge in the use of medicinal plants or phytogenic as feed additive in aquaculture.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the findings of this study demonstrate that CSE was able to modulate immunological parameters in the blood and intestinal non-adherent leukocytes of rainbow trout and sustain the anti-inflammatory role exercised by bioactive molecules, among which were polyphenols, in fish [71,83]. Certainly, part of the biological activity could be ascribed to the presence in CSE of GA and derivatives, whose anti-inflammatory, antioxidant, antiviral, and anticancer properties are known [72,83,84].…”
Section: Discussionmentioning
confidence: 64%
“…Another study indicated that dietary administration of an olive oil extract rich in tyrosol and hydroxytyrosol decreased MDA levels in muscle of gilthead sea bream (Sicuro et al, 2010). The majority of the available reports on PCs in aquaculture have mainly focused on their use as immunostimulants (Nootash et al, 2013;Magrone et al, 2016). Our data suggest that MPE PCs significantly mitigate lipid peroxidation in zebrafish, which merits further investigation in fish that are used for human consumption to validate their use as feed supplements conclusively.…”
Section: Lipid Peroxidationmentioning
confidence: 56%